Designing a potent L1 protein-based HPV peptide vaccine: A bioinformatics approach. (April 2020) - Yazdani, Zahra; Rafiei, Alireza; Valadan, Reza; Ashrafi, Hossein; Pasandi, MarziehSharifi; Kardan, Mostafa
Graphical abstract: Highlights: The vaccine consists of four major sections: toll-like receptor 4 adjuvant, toll-like receptor 5 adjuvant and two epitopes. Each section was joined together by appropriate linkers. Different strategies were applied to enhance immunogenicity of peptide vaccine. The vaccine is able to protection of population on all members of α-papillomaviridea family. The vaccine has a high quality structure and appropriate physicochemical properties in E. coli as host. Abstract: Background: Oncogenic human papilloma viruses (HPV) are the cause of various types of cancer, specifically cervical cancer. L1 protein is the main protein of HPV capsid which targeted in many vaccine-producing attempts. However, they have not enough coverage on the various high risk HPV types. Therefore, having a low cost potent HPV vaccine to protect against all members of the α-papillomaviridea family will be promising. In this study, L1 protein-based peptide vaccine was designed using immunoinformatics methods which provides physicochemical properties such as stability in room temperature, potential of antigenicity, non-allergic properties and no requirement with eukaryotic host system. Results: The designed vaccine has two HPV conserved epitopes with lengths 18 and 27 amino acids in all members of α-papillomaviridea. These peptides promote humoral and cellular immunity and INF-γ responses. In order to ensure strong induction of immune responses, Flagellin, a Toll like receptor 5(TLR-5) agonist, and a short synthetic toll like receptor 4 (TLR-4) agonist were also joined to the epitopes. Structure of the designed- vaccine was validated using Rampage and ERRAT and a high quality 3D structure of the vaccine protein was provided. Docking studies demonstrated an appropriate and stable interaction between the vaccine and TLR-5. Conclusions: The vaccine is expected to have a high quality structure and suitable properties including high stability, solubility and a high potential to be expressed in E.coli . High potentiality of the vaccine in inducing humoral and cellular immune responses, may be considered as an anti-tumor vaccine.